Five decades of research on capital budgeting – A systematic review and future research agenda - Mohammad Abedin (Research in International Business and Finance, 2022)
This study synthesizes and reviews the existing literature on capital budgeting (CB) practices and their application to theories, contexts, characteristics and methodology. It aims to identify the prevalent issues and gaps in the literature and provide potential avenues for future research. After comprehensive search and rigorous scrutiny, this review encompasses 185 articles. A systematic literature review (SLR), triangulated with the bibliometric method, is carried out, adopting a meticulous approach to achieve a comprehensive overview of the field. Based on cluster analysis, four distinct themes are identified. Additionally, a conceptual framework is developed that shows the antecedents, moderators and outcomes of research on capital budgeting. Grounded on the detailed content analysis, 11 actionable future research directions are proposed to advance this field of research.